Pharmacoeconomic analysis (CER) of Dulaglutide and Liraglutide in the treatment of patients with type 2 diabetes - Su, Yu; Zhang, Shuo; Wu, Zezhen; Liu, Weiting; Chen, Jingxian; Deng, Feiying; Chen, Fengwu; Zhu, Dan; Hou, Kaijian (Frontiers in Endocrinology, 2023)
Aim: To evaluate the treatment effect Fand pharmacoeconomic value of Dugaglutide in women with type 2 diabetes. Methods: Women (n=96) with type 2 diabetes recruited from June 2019 to December 2021 were randomized into two equal groups. The control group was treated with Liraglutide, and the observation group was treated with Dulaglutide, both for 24 weeks. The blood glucose levels, biochemical index, insulin resistance index (HOMA-IR), cost-effect ratio (CER), and drug safety were determined and compared between the two groups. Results: Blood glucose levels, the biochemical index, and HOMA-IR were lower in both groups after the treatment (P < 0.05), and there was no statistical difference in the blood glucose levels, biochemical index and HOMA-IR between the two groups (P > 0.05). The CER levels did not differ statistically between the two groups (P > 0.05). Both the cost and the incidence of drug side effects during solution injection were lower in the observation group than in the control group after 24 weeks of treatment (P < 0.05). Conclusion: Both Dulaglutide and Liraglutide can reduce blood glucose levels, improve biochemical index, and HOMA-IR levels in women with type 2 diabetes. Dulaglutide is more cost-effective and safe.